Carboxy-functionalized pH responsive capsule polymer particles fabricated by particulate interfacial photocrosslinking. Issue 37 (13th March 2022) - Kitayama, Yukiya; Harada, Atsushi
Abstract : Carboxy-functionalized capsule polymer particles possessing neutral-alkali pH responsive controlled release capability were newly fabricated by interfacial photocrosslinking of spherical photoreactive polymer particles. Abstract : pH-responsive capsule particles show promise for various applications, such as self-healing materials, micro/nanoreactors, and drug delivery systems. Herein, carboxy-functionalized capsule polymer particles possessing neutral–alkaline pH responsive controlled release capability were newly fabricated by interfacial photocrosslinking of spherical photoreactive polymer [poly(2-carboxyethyl acrylate- co -2-cinnamoylethyl methacrylate): P(CEA-CEMA)] particles and a subsequent encapsulation process. Using P(CEA-CEMA) particles, the shell-crosslinked hollow polymer particles were fabricated by the particulate interfacial photocrosslinking procedure. Furthermore, the encapsulation of sulforhodamine B as a model dye into the hollow particles was also performed. Under acidic pH conditions, encapsulated molecules were stably retained in the P(CEA-CEMA) capsules with negligible release of sulforhodamine B. However, the encapsulated sulforhodamine B was gradually or drastically released from the capsule particles under neutral or basic conditions, respectively, indicating that the neutral–alkaline pH responsive controlled release from the capsules was successfully achieved by regulating the release kinetics. These results demonstrate that the fabrication routes of hollow and capsule particles based on particulate interfacial photocrosslinking can be successfully applied to carboxy-functionalized photoreactive polymer particles, and the capsule polymer particles possessing pH-responsive release properties under neutral–basic conditions were successfully fabricated.